A flying goose chase: China's overseas direct investment in manufacturing (2011–2013). Issue 2 (4th May 2018) - XU, Jiajun; Hubbard, Paul
ABSTRACT: This paper examines whether rising wages have driven Chinese manufacturers to make foreign direct investment abroad to reduce the costs of production. We match the Chinese Ministry of Commerce's register of Overseas Direct Investments with China's Industrial Enterprise Survey data from 2011 to 2013 and annual average wage data for prefecture-level cities. Although high-income developed economies are the preferred destinations for Chinese manufacturing investment abroad, labor-intensive light manufacturing sectors related to the textiles, clothing and leather industries are focused on the low-income countries – consistent with a 'flying goose' effect. But, these are only a small part of the Chinese investment – account for 6% of the number of matched official ODI registrations. Yet, it might be still too early to observe that rising factor prices are systematically driving investments offshore.